Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/brb3.1333
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant patterns of default‐mode network functional connectivity associated with metabolic syndrome: A resting‐state study

Abstract: IntroductionMetabolic syndrome (MetS) is a clustering of three or more cardiovascular risk factors (RF), including hypertension, obesity, high cholesterol, or hyperglycemia. MetS and its component RFs are more prevalent in older age, and can be accompanied by alterations in brain structure. Studies have shown altered functional connectivity (FC) in samples with individual RFs as well as in clinical populations that are at higher risk to develop MetS. These studies have indicated that the default mode network (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 102 publications
1
9
0
Order By: Relevance
“…Previously, it has been shown that higher levels of blood cholesterol and diastolic blood pressure were associated with a reduction of RSFC over time in the DMN and in global RSFC, respectively ( Köbe et al, 2021 ). Together, the earlier and present longitudinal findings converge very well with the existing (mostly cross-sectional) studies, indicating a greater vulnerability of higher-order brain networks to a variety of VRF including higher levels of blood pressure, cholesterol, and HbA1c as well as the metabolic syndrome ( Li et al, 2015 ; Zhang et al, 2016 ; Rashid et al, 2019 ; Feng et al, 2020 ; Veldsman et al, 2020 ). As in the previous study ( Köbe et al, 2021 ), a similar association was not found for BMI.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, it has been shown that higher levels of blood cholesterol and diastolic blood pressure were associated with a reduction of RSFC over time in the DMN and in global RSFC, respectively ( Köbe et al, 2021 ). Together, the earlier and present longitudinal findings converge very well with the existing (mostly cross-sectional) studies, indicating a greater vulnerability of higher-order brain networks to a variety of VRF including higher levels of blood pressure, cholesterol, and HbA1c as well as the metabolic syndrome ( Li et al, 2015 ; Zhang et al, 2016 ; Rashid et al, 2019 ; Feng et al, 2020 ; Veldsman et al, 2020 ). As in the previous study ( Köbe et al, 2021 ), a similar association was not found for BMI.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, regions projecting positively into the leading eigenvector in the DBS-state, such as the anterior cingulate cortex [37]–[39], middle frontal gyrus [40], inferior parietal cortex [38], [40], [41], isthmus cingulate cortex [42], orbitofrontal cortex [38], middle temporal gyrus [40], [43], [44], precuneus cortex [37], [39], [40], superior frontal gyrus [45]– [47], and thalamus [37] are reported in the literature as part of the DMN. Moreover, owing to that the DBS-state comprises many frontoparietal areas, including the superior frontal gyrus (coincident with the pre-supplementary motor area) [48], middle frontal gyrus, middle temporal gyrus, inferior parietal cortex [46], [49], and precuneus [46], [47], it makes sense that this PL state also significantly correlates with the FPN.…”
Section: Resultsmentioning
confidence: 99%
“…The DBS-state comprises an extensive network of intrinsic functional connectivity consisting of distinct brain regions commonly reported as part of the DMN such as the anterior cingulate cortex [37]- [39], middle frontal gyrus [40], inferior parietal cortex [38], [40], [41], isthmus cingulate cortex [42], orbitofrontal cortex [38], middle temporal gyrus [40], [43], [44], precuneus cortex [37], [39], [40], superior frontal gyrus [45]- [47], and thalamus [37].…”
Section: Stn-dbs Modulates the Dmn In Patients With Pdmentioning
confidence: 99%
“…In addition, we further revealed the different cerebello-DMN connection pattern between SCZ-nMetS and SCZ-MetS. On the other hand, DMN also appeared to be especially vulnerable to metabolic abnormalities [ 55 , 56 ]. Disrupted resting state FC within DMN related to burden of vascular was implicated in cognitive function [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, DMN also appeared to be especially vulnerable to metabolic abnormalities [ 55 , 56 ]. Disrupted resting state FC within DMN related to burden of vascular was implicated in cognitive function [ 56 , 57 ]. Overall, cerebellar-DMN FC could, respectively, underlie two possible patterns of mechanism: change of psychiatric symptom and adverse influence of metabolic syndrome on cerebral connectivity states.…”
Section: Discussionmentioning
confidence: 99%